KEMAJUAN SELEKSI KOMPONEN HASIL KEDELAI (Glycine max L. Merr.) F4 HASIL PERSILANGAN GROBOGAN DENGAN GALUR KM19 DAN KM25 - Fikri, Ariful; Rasyad, Aslim; Hamzah, Anthony (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
The soybean population of F4 strain descended from a cross between Grobogan varieties with KM19 and KM25 lines aims to observe the selection progress of several lines selected from the F3 population in the Faculty of Agriculture Experimental Garden, Riau University. The experimental design in the field used a randomized block design with 4 replications, the treatment consisted of 20 different soybean genotypes and 3 elders, thus there were 72 experimental plots measuring 300 cm x 100 cm, with a spacing of 20 cm x 30 cm. The parameters observed in this study were plant height, number of branches, age of flowering, age of harvest, seeds per pod, seeds per plant. seed weight per plant, weight 100 seeds, total pods, pith pods, yield per m2 and harvest index. Harvest age has a high heritability value, while the parameters of plant height, total pods, pod pods, number of seeds per plant, weight of seeds per plant, flowering age have moderate heritability values which means inheritance of these parameters in the next generation is not too large. The number of branches, seeds per pod, weight of 100 seeds and harvest index, has a low heritability value. The largest selection response value is the yield character per m2 that is equal to 46.04%, which means that each selection cycle using the yield criteria per m2 will change the middle value of 46.04%. Next there will be a change in the middle value of 33.47% in the number of seeds per plant, followed by a change in the middle value of 4.10% at the age of harvest, then a change in the mean value of the pods of 10.32%, followed by a change in the mean value seeds per plant is 33.47%, and the change in the mean value of the total number of pods is 10.75% if selected with criteria for the number of seeds per plant, age of harvest, number of pods in a row, and number of seeds per plant in a row. Keywords: Soybean, variability, selection, heritability,